Study of the Coulomb Nuclear Interference of 23Al Breakup Reaction with Different Targets - Surender; Kumar, Ravinder (East European Journal of Physics, 2024)
The impact of Coulomb-diffraction interference on the one-proton removal breakup cross-section and the width of the longitudinal momentum distribution (LMD) has been investigated for the breakup reaction of the $^{23}$Al nucleus with different light to the heavy target for energy 40-100MeV/nucleon. Sensitivity to the target size and incident energy was analyzed through calculations that incorporate Coulomb interactions to all orders, including the full multipole expansion and nuclear diffraction using the eikonal approximation in the Glouber model. The results indicate that both constructive and destructive interferences significantly impact the observables, with the effects being more pronounced for medium-mass targets than light or heavy targets.